(untitled) (International Journal of Occupational Safety and Health, 2022)
Introduction: Post-traumatic stress disorder usually occurs after a traumatic event and this COVID-19 pandemic has affected mental health to a great extent. While there is extensive research being conducted about this aspect among the general population, the most neglected are the Industrial workers during the first lockdown period. The aim of the study was to assess the risk of post-traumatic stress disorder symptoms using the impact of event scale-revised (IES-R), their main stressors and coping measurements among the industrial workers of Hyderabad. Methods: A telephonic interview schedule was adopted to fill the online questionnaire among Industrial workers of age group 20-55 years during the lockdown period. Hundred and seventy-four participants were included in our study and data was collected using standardized tools IES-R and brief resilient coping scale. Various stressors and also their coping strategies were elucidated. Results: At the risk of post-traumatic stress disorder symptoms were found among 20.6% and at risk of suppressed immune system functioning which is presumed to have its effect for the next 10 years was 13.8%. The main stressors of COVID-19 with increased IES-R score were not staying with family members, influence of social media, Any acquaintance with COVID-19 infected person effect on daily life and white-collar group. Coping measurements with a brief resilient coping scale found 17.4% as low resilient copers. Conclusion: This identification of high-risk post-traumatic stress disorder symptoms needs to be addressed earlier to bring up preventive strategies such as counseling services in the occupational health care centers of our industries.